Interactive bengali games using multi-modal communication for autistic children of Bangladesh - Anjum, Rafia; Islam, Tamanna (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.